The Influence of Agile Leadership, Resilience and Technology Sensing on Employee Performance with Employee Well Being as an Intervening Variable on State Civil Apparatus (ASN) Employees at the Forestry Service of East Java Province - Hartadi, Arif; Mujanah, Siti; Ardiana, I .D. Ketut Raka (International Journal of Economics (IJEC), 2025)
The Forestry Service has the task of organizing part of the provincial government affairs in the forestry sector based on the principle of autonomy which is the authority, deconcentration and assistance tasks, and other tasks in accordance with the policies set by the Governor based on applicable laws and regulations. According to the Regulation of the Governor of East Java No. 84 of 2016, the Forestry Service is an implementing element of government affairs in the forestry sector led by the Head of the Service who is positioned under and responsible to the Governor through the Regional Secretary of East Java Province.The problems that still arise in the organization are the declining work spirit of employees, due to the rapid development of the use of information technology (more sophisticated), and the level of communication and Employee Well Being is still relatively poor. This study was conducted to fill this gap, and create a model with Employee Well Being as an intervening variable, which has not been widely studied, especially ASN in the forestry sector. The purpose of this study was to determine the effect of agile leadership, resilience and technology sensing on employee performance with employee well being as an intervening variable on State Civil Apparatus (ASN) Employees at the East Java Provincial Forestry Service. This study uses a quantitative method with primary data sources obtained from distributing questionnaires. The population of this study was all employees at the East Java Provincial Forestry Service. Respondents were selected using a saturated non-probability sampling method, totaling 100 participants. Data analysis involved descriptive analysis and SEM-PLS analysis. The study finds that agile leadership, resilience, and technology sensing positively and significantly impact employee performance by improving employee well-being among ASN employees at the East Java Provincial Forestry Service.